NATIONAL-PATRIOTIC EDUCATION OF STUDENTS IN INSTITUTIONS OF OUT-OF-SCHOOL EDUCATION OF THE ECOLOGICAL AND NATURAL DIRECTION - Machuskyi, Valerii (Theoretical and Methodical Problems of Children and Youth Education, 2024)
The article is devoted to one of the urgent problems of modern pedagogical science – the organization of national-patriotic education of students in out-of-school educational institutions of ecological and natural direction. The purpose of the article is to analyze the data obtained as a result of a theoretical and empirical study of the organization of national-patriotic education of students in extra-curricular ecological and naturalistic educational institutions, which will become the basis for the preparation of methodological recommendations for methodologists and teachers of extra-curricular education institutions during the implementation of proper educational work with students The task of the research: to analyze the state of the problem of national-patriotic education of students in extracurricular educational institutions of ecological and naturalistic direction; clarify the essence and structure of the concept of “national-patriotic education of a student of an out-of-school educational institution of ecological and natural direction”; to characterize the content, forms, methods and techniques of national-patriotic education of students in ecological and naturalistic out-of-school educational institutions and experimentally verify their effectiveness. In the research process, the following methods are used: theoretical analysis of psychological and pedagogical literature, study and generalization of innovative pedagogical experience of the organization of national-patriotic education of students in out-of-school educational institutions of the ecological and natural direction, pedagogical observation, conversations, questionnaires, surveys, systematization and classification of the received mass of information, methods of comparative analysis, interpretation and generalization of data. Determination of the features of this process, appropriate analysis, and generalization of the data obtained as a result of empirical research is the basis of the development of the methodology for the organization of national-patriotic education of students in out-of-school educational institutions of ecological and natural direction. It has been established that in connection with the war in pedagogical science, the problems of developing and implementing in the educational process of out-of-school institutions of national-patriotic education of students of person-oriented modern pedagogical technologies and methods aimed at forming national-patriotic education become especially relevant. The essence of the definition of national-patriotic education, which we consider a gradual and steady formation of love for one’s Homeland in children and student youth, has been clarified. The components of the national-patriotic education of students of out-of-school educational institutions of ecological and natural direction (cognitive, emotional, behavioral) are determined.